Adsorption of Chromium(Vi) onto Electrochemically Obtained Magnetite Nanoparticles - Recio-Cortes, F; Recio-Cortes, F (Center for Environmental and Energy Research and Studies, 2015)
Well-dispersed magnetite nanoparticles of different sizes between 15 and 43 nm were synthesized by an electrochemical method in a controlled manner by simply changing the synthesis temperature. These nanoparticles were used as a reusable adsorbent to remove Cr(VI) from aqueous solution. The recovery efficiency was found to be highly dependent on environmental parameters, such as temperature and pH. In addition, it was demonstrated that the initial concentrations of both Cr(VI) and magnetite nanoparticles strongly influence the removal capability of these nanomaterials. Remarkably, the nanoparticle size has a key role on the Cr(VI) adsorption efficiency, which gradually increases as the diameter decreases due to the augmentation of the surface area. The low aggregation in the case of small particles that results from the low magnetization saturation values also contributes to the enhancement of the surface area available for Cr(VI) adsorption. In contrast, nanoparticles with larger sizes are more easily manipulated by a magnet, and the efficiency is largely maintained after five cycles. The adsorption process fits the Langmuir isotherm model well, and the reaction was found to follow a pseudo-second-order rate. © 2015, Islamic Azad University (IAU).